Exploring the Influence of Technology on EFL Learning: A Comparative Analysis of Introverted and Extroverted Students - Syukron Fajriansyah (Studies in Language, Education, and Culture (SeLEC), 2025)
This study examines the impact of technology on English as a Foreign Language (EFL) learning, specifically focusing on the utilization of technology by introverted and extroverted students. The objective is to provide a comprehensive overview of how technology is employed as a learning tool and to identify potential disparities between the two student groups. A descriptive research design was adopted, and qualitative analysis was used for data interpretation. The participants included introverted students and extroverted students, who were interviewed online using WhatsApp media. The findings indicate that both introverted and extroverted students employ technology, particularly learning videos, to enhance their language skills. However, introverted students tend to prefer using technology alone compared to their extroverted counterparts. These results offer insights into the differences between introverted and extroverted learners in utilizing technology for EFL learning. The study contributes to the existing literature on individual learner differences, with a specific focus on the use of technology by introverted and extroverted students in the EFL context.